Pengaruh Perputaran Kas, Perputaran Piutang, Dan Perputaran Persediaan Terhadap Profitabilitas Dengan Likuiditas Sebagai Variabel Intervening - Tsari Bunga Hariri; Titin Agustin Nengsih; Marissa Putriana (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine and test the effect of cash turnover, accounts receivable turnover and inventory turnover on profitability with liquidity as an intervening variable, case studies in plastic and packaging sub-sector companies listed on the IDX for the 2019 – 2022 research year. This research is a quantitative study using secondary data, namely financial report data in the form of balance sheets, income statements, and cash flow reports. The variables used include cash turnover, accounts receivable turnover, and inventory turnover as independent variables while profitability as the dependent variable and liquidity as intervening variables. For the profitability variable, the research uses the Return On Asset ratio, while the liquidity variable uses the current ratio. The sample companies used were 11 companies listed on the IDX in the plastics and packaging subsector. This research method is quantitative (classical assumption test: normality test, multicollinearity test, heteroscedasticity test) and multiple linear regression analysis. While testing the hypothesis using path analysis.The results of this study are that there is only one variable that influences profitability, namely the cash turnover variable. Meanwhile, in the liquidity variable, there are two influential variables, namely the cash turnover variable and the profitability variable.